Pembiayaan Mudharabah Sebagai Alternatif Pendanaan Bagi Pelaku Industri Halal - Aireni Ratnasari; Syukron Suwardi; nur irmandi (STAI Al-Mas'udiyah, 2024)
Flexibility in determining profit sharing ratios and a focus on integrity and transparency in fund management provide distinct advantages in this approach. In addition, Mudharabah financing helps halal industry players avoid riba and speculation, which is consistent with Islamic ethical principles. In the economic impact analysis, it was revealed that Mudharabah financing can promote the growth of the halal industry and make a positive contribution to overall economic growth. This becomes relevant in the context of an industry known for its sanctity and halal. Thus, this journal details the benefits and potential of Mudharabah financing as a sharia-based funding instrument for halal industry players. This financing provides solutions that are fair, sustainable, and in line with the values of Islamic business ethics, which can provide support for the development of the halal industry and inclusive economic growth